Impacto of osteoporosis on the quality of life of the enderly (Research, Society and Development, 2024)
Introduction: Osteoporosis is a systemic bone metabolism disease characterized by a decrease in bone mineral density and deterioration of the bone tissue microarchitecture, increasing bone fragility and the risk of fractures. It mainly affects postmenopausal women and the elderly, but it can also affect men and younger individuals under specific conditions. Objective: This study investigates the main risk factors for the development of osteoporosis. Methodology: This is an integrative literature review analyzing scientific publications from 2021 to 2024 on the topic. The search was conducted in the PubMed, SciELO, Google Scholar, and LILACS databases. Twenty-two articles were identified, of which 20 met the established criteria. Results and Discussion: Genetic factors are important, but lifestyle, such as a calcium-poor diet and physical inactivity, and clinical conditions, such as prolonged use of corticosteroids, also contribute to the development of osteoporosis. Early identification through bone densitometry and laboratory tests is essential to prevent complications. Strategies such as calcium and vitamin D supplementation, combined with physiotherapy and resistance exercises, promote mobility, strengthen bones, and reduce falls. Multidisciplinary interventions and public policies focused on health education are essential to improve the quality of life for the elderly. Conclusion: Osteoporosis significantly impacts the quality of life of the elderly, requiring early diagnosis, awareness, and multidisciplinary interventions. The implementation of public policies and preventive programs is essential to foster autonomy and well-being in this age group.